Challenges and Opportunities in the Policy and Practice of Inclusive Education in Madrasah Ibtidaiyah: Evidence from Cirebon Regency, Indonesia - Shulkhah Shulkhah; Sofyan Mustoip (EduBase : Journal of Basic Education, 2026)
Inclusive education has become a global priority aligned with Sustainable Development Goal 4 (SDG 4); however, its implementation in Islamic primary schools remains underexplored, particularly in the context of Madrasah Ibtidaiyah (MI) in Indonesia. Objective: This study aims to examine the challenges and opportunities in the policy and practice of inclusive education in Madrasah Ibtidaiyah in Cirebon Regency, Indonesia. Novelty: This study contributes to the limited body of research on inclusive education in Islamic primary school contexts by providing empirical evidence from Madrasah Ibtidaiyah, highlighting the intersection between policy and practice in a local Indonesian setting. Method: A qualitative case study approach was employed. Data were collected through interviews, observations, and document analysis, and analyzed using thematic analysis with triangulation to ensure validity. Results: The findings reveal that the primary challenges include limited teacher competencies in inclusive pedagogy, inadequate disability-friendly infrastructure, insufficient curriculum adaptation, and persistent social stigma. Additionally, gaps between policy and practice hinder effective implementation. However, opportunities emerge through increased access to professional development programs, growing awareness of inclusive values, and strengthened collaboration among schools, families, and local communities. Conclusion: Strengthening teacher capacity, improving resources, and enhancing multi-stakeholder collaboration are essential to advancing inclusive education and achieving equitable learning outcomes.